ANALISIS RASIO KEUANGAN TERHADAP INCOME SMOOTHING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2016 - Theresia Alfita Cahyaningrat, Bambang Widarno & Fadjar Harimurti (Universitas Slamet Riyadi, 2019)
The objectives of this research are (1) The effect of return on asset to income smoothing, (2) The effect net profit margin to income smoothing, (3) The effect of financial leverage to income smoothing and (4) The effect of income tax to income smoothing. The population in this research is all the banking companywhich listed in the Indonesian Stock Exchange 2014 - 2016. Sampling technique used in this research is purposive sampling, with the sum of the sample 28 firm. Double linier regression is used as data analysis technique, both t test and F test. The results of this research are (1) Return on asset variable have positive affects and not significant influence on the income smoothing, (2) The net profit margin have not significant influence on the income smoothing (3) Financial leverage have not significant influence on the income smoothing and (4) Income tax havenot significant influenceon the income smoothing.Keywords: return on asset, net profit margin, financial leverage, income tax, income smoothing.